Analisis Model Bisnis Untuk Brand Skincare Dalam Upaya Menciptakan Keunggulan Bersaing Konteks Ekonomi Islam (Studi Pada Brand Lamooi Beautycare) - Oktavani, Tiara Siska; Raharjo, Susilo Toto (ITB AAS INDONESIA Surakarta, 2024)
This research aims to conduct a business model analysis of Lamooi Beautycare, a newcomer to the highly competitive skincare industry. Despite receiving positive recognition from customers, Lamooi Beautycare faces the challenge of establishing a competitive edge amidst the dynamic skincare market. The study seeks to identify internal and external factors influencing the current skincare industry and formulate business development strategies that enhance the company's competitive advantage. The research methodology employs a qualitative approach with a case study design. Sampling in this study used purposive sampling. In this research, the informants used as research subjects were the Beauty Company/Brand, namely Lamooi Beautycare, with 3 respondents, namely the owner of the beauty brand to be researched, a marketing employee, and an admin. The Resource-Based View (RBV) framework will be utilized to analyze internal factors, complemented by the Five Forces Porter framework for the analysis of external factors. Additionally, the study will incorporate the Business Model Canvas (BMC) to formulate a comprehensive business development strategy. Through this analysis, the research aims to provide a profound understanding of the skincare industry's dynamics, evaluate critical factors influencing Lamooi Beautycare's success, and develop precise strategies to achieve competitive advantage. By gaining a better understanding of internal and external factors, Lamooi Beautycare is expected to optimize its internal potential, leverage market opportunities, and navigate competitive challenges, ultimately realizing its vision and mission while expanding its business in this fiercely competitive era. The existing strategy that is/has been implemented by the owner of the Lamooi Beautycare Brand is in accordance with the nine elements in the Business Model Canvas, namely, Customer Segments, Value Propositions, Customer Relationships, and Key Resources